Islamic Rules and Strategies to Bring Peace in Community - Fath ul Rahman Qurashi; Abdelhamid Kharroub; Noura Zouai; Masood Ahmed (Institute of Business Management, 2019)
Islam aims to achieve peace and security in the humanitarian community and prevents it from all the fearful causes that surround the Muslim community and non-Muslim on the face of the earth. This case study attempts to highlight the most important Islamic rules and strategies for peacebuilding in the community by discussing the rules of peace in Islam and the strategies for peace in the community. The findings of the study reveal that true faith instils in the soul of human goodness and fairness, which prevents him from evil. This faith deprives him of injustice and corruption in the earth. The disbelief in God and turning away from his remembrance is the source of fear and misery, worries and problems, distress in the livelihood, deprivation of moral and material security.  To achieve the peace in the community, six key strategies are necessary including holding the Book (Quran) and Sunnah (Consistent way of the Prophet), fighting the ingratitude towards the bounties, understanding the Islam towards the phenomenon of hypocrisy and hypocrites, managing pluralism in Islam, understanding the strategic distribution of wealth among the people, and finally administrating of justice and the prohibition of injustice.